Modeling the mechanisms of the functioning of the logistics distribution system - Burkov, V; Akhmetkaliyeva, S; Mukhtar, Y (Farabi Journal of Social Sciences, 2019)
Currently, the use of the concept of logistics in inventory management is considered by enterprises as one of the reserves to achieve a competitive advantage. In theory, inventory control deficit arises due to insufficient supply, unreliable source of supply, and because of inaccurate information provided by customers to suppliers. The solution to this problem consists in finding a compromise between the cost of creation of material stockpiles and storage costs, and the creation of the mechanisms of management of active systems, elements of which are suppliers and customers. The implementation of the control mechanisms of the two-level system supplier-consumer, we have considered the example of the game-theoretic model. For the consistency of the idea considered in the article, it should be emphasized that in the supply chain-each customer-consumer is also a supplier in an orderly sequence of suppliers and consumers, as long as the product does not reach the end user. In this article, the simulation game tool in the context of hierarchical games is used to simulate the simplest scheme of the logistics distribution system. In the process of realization of finished products the model of distribution logistics between the supplier and the consumer enterprises is considered. The case of deficit is simulated when the total volume of customers ‘ orders for early delivery exceeds the production capacity of the supplier. The main purpose of the article is to give a clear idea of the functioning mechanisms used in the management of the distribution system of logistics, as well as to provide distribution logistics specialists with the possibility of effective solutions in the process of distribution of finished products in a deficit. Key words: distribution logistics, functioning mechanisms, game-theoretic model, supplier, consumer.